2018
DOI: 10.1016/j.ijrobp.2017.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Effect of 3T Magnetic Resonance Imaging Residual System Distortions and Patient-Induced Susceptibility Distortions on Radiation Therapy Treatment Planning for Prostate Cancer

Abstract: Patient-induced susceptibility distortions at high field strengths in closed bore magnetic resonance scanners are larger than residual system distortions after using vendor-supplied 3-dimensional correction for the delineated regions studied. However, errors in dose due to disturbed patient outline and shifts caused by patient-induced susceptibility effects are below 0.5%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…In MRI‐guided radiotherapy treatment, geometric distortions can translate into dosimetry uncertainties . The clinical dosimetry accuracy is normally evaluated by using the steepest dose–response curves for normal tissue complication probability and for tumor control probability (TCP) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In MRI‐guided radiotherapy treatment, geometric distortions can translate into dosimetry uncertainties . The clinical dosimetry accuracy is normally evaluated by using the steepest dose–response curves for normal tissue complication probability and for tumor control probability (TCP) .…”
Section: Discussionmentioning
confidence: 99%
“…In MRI-guided radiotherapy treatment, geometric distortions can translate into dosimetry uncertainties. 42 The clinical dosimetry accuracy is normally evaluated by using the steepest dose-response curves for normal tissue complication probability and for tumor control probability (TCP). 43 The geometric inaccuracy of the target will potentially decrease the tumor control probability or overlap regions with the adjacent healthy structures, which could be detrimental for patients in terms of normal tissue complications.…”
Section: Discussionmentioning
confidence: 99%
“…Based on their simulation and using vendor‐corrected MR images, they found that MR distortions can lead to <4% of the target volume coverage loss and potential increased doses to organs at risk of 5–6 Gy. In another recent study, Adjeiwaah et al estimated <0.5% difference in the PTV dose in prostate cancer patients arising from residual system and patient induced susceptibility distortions . Data are still emerging to determine the acceptable magnitude of geometric distortions for MRgRT.…”
Section: Discussionmentioning
confidence: 99%
“…In another recent study, Adjeiwaah et al estimated <0.5% difference in the PTV dose in prostate cancer patients arising from residual system and patient induced susceptibility distortions. 13 Data are still emerging to determine the acceptable magnitude of geometric distortions for MRgRT. More specifically, recommendations for GNL distortion accuracy are not currently well defined for MRgRT and are currently being addressed in AAPM TG-284 for MR simulators and MRIs sited in Radiation Oncology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation